Comments on proper type designation for names of taxa validated by Turczaninow in his Animadversiones, with case studies - Mosyakin, S.L.; McNeill, J.; Boiko, G.V. (Український ботанічний журнал, 2019)
General recommendations regarding proper type designation of names of taxa described by Turczaninow in his Animadversiones series
of articles (as well as in some other publications) are provided. It is concluded that, as clearly indicated in the protologues, all (or almost all)
taxa described in these publications are based on specimens from the private herbarium of Turczaninow which was donated in the 1840s to the
Kharkiv University (CWU) and in the 1940s was transferred to the Institute of Botany in Kyiv (KW). Consequently, holotypes and syntypes of
these taxa are now almost exclusively in KW. Several cases of correct and incorrect type designations are discussed, specifically of some South
American Brassicaceae, Geraniaceae and Hypericaceae, Central American Malvaceae, and southern African Polygalaceae. Information on the
re-discovered holotype (KW) of Abelmoschus achanioides Turcz. (now accepted as Malvaviscus achanioides (Turcz.) Fryxell, Malvaceae) is
provided, and an earlier lectotypification of that name with a specimen from G is considered ineffective. The holotype of Stenocalyx involutus
Turcz. (now considered a synonym of Mezia includens (Benth.) Cuatrec., Malpighiaceae) was originally in the Turczaninow herbarium, but
the whole folder with that specimen is now missing in KW (considered lost or destroyed), and it was already missing in the mid-1920s, when
the collection was still in CWU. Because of that the lectotype of S. involutus is designated here, the specimen from MPU, to replace the lost
or destroyed holotype. The need for thorough analysis of protologues, available original material, and associated information for correct type
designation/indication is emphasized. Наведені загальні рекомендації щодо правильного позначення типів назв таксонів, що були описані М.С. Турчаніновим у серії статей "Animadversiones…" (а також у деяких інших його публікаціях). На основі чітких вказівок у протологах зроблено висновок про те, що усі (або майже всі) таксони, описані в цих публікаціях, базуються на зразках з приватного гербарію Турчанінова, який у 1840-х роках був подарований ним Харківському університету (CWU), а у 1940-х роках переміщений до Інституту ботаніки у Києві (KW). Отже, голотипи та синтипи цих таксонів зараз знаходяться майже виключно у гербарії KW. Обговорюються декілька випадків правильних та неправильних позначень типів, зокрема, для деяких південноамериканських представників родин Brassicaceae, Geraniaceae та Hypericaceae, центральноамериканських Malvaceae та південноафриканських Polygalaceae. Наведена інформація про віднайдений у KW голотип Abelmoschus achanioides Turcz. (зараз визнаний під назвою Malvaviscus achanioides (Turcz.) Fryxell, Malvaceae), а попередня лектотипіфікація цієї назви зразком з гербарію G визнана недійсною. Голотип Stenocalyx involutus Turcz. (нині розглядається як синонім визнаної назви Mezia includens (Benth.) Cuatrec., Malpighiaceae) раніше знаходився у гербарії Турчанінова, але всієї папки з цим зразком у KW зараз немає; вона вважається втраченою і вже була відсутня у середині 1920-х років, коли колекція ще перебувала в CWU. З цієї причини назва S. involutus лектотипіфікована тут зразком з гербарію MPU, на заміну втраченого або знищеного голотипу. Наголошується на необхідності ретельного аналізу протологів, наявного оригінального матеріалу та асоційованої інформації для правильної типіфікації.